Preparing Business Education Teachers for Effective Implementation of Student-Centred Learning Strategies in the E- World - Olusegun EEBO, Timothy; ADEMILUYI, L.F. (International Journal Of Management And Economics Invention, 2022)
This paper highlights preparing business education teachers for effective implementation of student-centred learning strategies in the e- world. The paper defines terminologies such as Student-centred learning, e-learning and the need for linking ICT to education policies. It examines the world links program with student-centered teaching and learning web sites as well as discusses main characteristics of student-centered strategies and its popular types. It further discusses learning situations in the field of business education, teacher’s role in student-centred strategies with implication of using student-centred strategies in Nigeria business education programme and analysis of threats to student-centred strategies. The paper concludes by making recommendation on the way forward among which Teacher should encourage student interaction in utilizing e-libraries or e-world at large in class participations. Institutions should encourage teachers in using student-centre strategies by sending them to seminal, conference/ workshop that base on this purpose. And institution should make available internet service 24/7 with power supply in the schools and staff quarters.